UJI TEKNIS PENCAHAYAAN RUANG KELAS DI SALAH SATU SMK NEGERI DI KOTA MALANG MENGGUNAKAN ALAT LUX METER BERDASARKAN STANDAR SNI 6197:2011 - Ariffa Rahayu; Eko Suwarno; Arsyad Agus Al Muzamil; Artha Vanja Saktiyan; Astrela Regina Shirley Uma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Classroom lighting is an essential factor in supporting visual comfort and the effectiveness of the learning process. Inadequate lighting intensity can lead to eye fatigue, decreased concentration, and reduced learning performance among students. This study aims to analyze the lighting level of a classroom in one of the public vocational high schools in Malang City using a lux meter and to compare the results with the Indonesian National Standard SNI 6197:2011. This research employed a quantitative approach with a descriptive design. Data were collected through direct measurements at 64 points representing different classroom areas, including the front, middle, back, and both sides. The data were analyzed using descriptive statistics to obtain mean, minimum, maximum, and standard deviation values.The results showed that the average lighting intensity was 24.34 lux, with a minimum value of 9.0 lux and a maximum value of 49.5 lux. These values are significantly below the minimum standard of 350 lux as required by SNI. In addition, the lighting distribution was uneven, as indicated by variations across measurement points. All measurement points (100%) fell into the very low category (<100 lux), indicating that the classroom lighting condition does not meet the required standards. Factors contributing to the low lighting level include insufficient number of lamps, uneven light distribution, and suboptimal utilization of natural lighting.This study recommends a comprehensive improvement of the lighting system, including the addition of light sources, rearrangement of lamp placement, and optimization of natural lighting to enhance visual comfort and the quality of the learning process